Quercetin Inhibits KBM7R Cell Proliferation through Wnt/β-Catenin Signaling. (24th June 2022) - Li, Wei; Yu, Yang; Cheng, Huanchen; Liu, Shengwei; Gong, Tiejun; Ma, Jun; Tang, Qinghua
Abstract : Background . Tyrosine kinase inhibitors could treat chronic myelogenous leukemia (CML) effectively, but they have no effect on patients with T315I mutation. It is necessary to find drugs to overcome the resistance. Quercetin (Qu) is a kind of bioflavonoid with an antitumor effect. In this study, we observed the effect of Qu on proliferation and Wnt/ β -catenin pathway in KBM7R cells, an imatinib-resistant cell with T315I mutation. Methods . The IC50 of Qu was detected by trypan blue staining. The KBM7R cell apoptosis and cycle were detected through the method of flow cytometry (FCM). The expression of the related mRNA and protein was evaluated by means of an RT-PCR assay and western blot in KBM7 (sensitive to IM) and KBM7R cells. Results . These results showed that in the KBM7R cell, the proliferation inhibition effect was increased after 48 h administration with different Qu concentrations. The IC50 to Qu was 241.7 μ mol/L. The different doses of Qu (50, 100, and 200 μ mol/L) would raise apoptosis and depress the cell cycle at the G1 phase. Dealing with a median Qu concentration (100 μ mol/L) for 48 h, the mRNA and the protein level of caspase-3, caspase-8, and caspase-9 along with p21 and p27 raised compared with the control. The median concentration of Qu could inhibit both the mRNA and protein levels of GSK-3 β, β -catenin, and Lef-1 in the Wnt/ β -catenin signal pathway and also the downstream targets PPAR- δ and cyclin D1 in both KBM7 and KBM7R cells. Conclusions . Our findings suggest that Qu could inhibit proliferation, induce apoptosis, and arrest the cell cycle on IM-resistant KBM7R cells with T315I mutation. And this effect could be related with the inhibition of the Wnt/ β -catenin signal pathway and downstream targets.